THE INFLUENCE OF ENVIRONMENTAL POLICY ON BUSINESS SUSTAINABILITY IN INDONESIA: LEGAL AND ECONOMIC PERSPECTIVES - Haspada, Deny (AKSELERASI: Jurnal Ilmiah Nasional, 2022)
This study explores the impact of environmental policies on business sustainability in Indonesia, integrating legal and economic perspectives to provide a comprehensive analysis. The research addresses the critical question of how environmental regulations influence business operations, profitability, and compliance within the Indonesian context. Utilizing a mixed-methods approach, including qualitative case studies and quantitative data analysis, the study reveals significant findings. Firstly, stringent environmental regulations impose additional costs on businesses, affecting short-term profitability. However, they also promote long-term sustainability by encouraging eco-friendly practices and innovation. Secondly, the legal framework in Indonesia, while robust, faces challenges in enforcement and compliance, leading to varying levels of adherence among businesses. The study’s novelty lies in its interdisciplinary approach, combining legal analysis with economic evaluation to offer holistic insights into the interplay between regulation and business sustainability. The findings have important implications for policymakers and business practitioners. For policymakers, the study underscores the need for balanced regulations that support environmental goals without stifling economic growth. For businesses, the research highlights the importance of proactive compliance and the potential competitive advantages of sustainable practices. This study contributes to the ongoing discourse on sustainable development and provides a foundation for future research on environmental policy impacts in emerging economies.